Programming Python - Lutz, Mark (O'Reilly, 2006)
Already the industry standard for Python users, ProgrammingPython fromO'Reilly just got even better. This third edition has been updated toreflect current best practices andthe abundance of changes introduced by the latest version of thelanguage, Python 2.5. Whether you're a novice or an advancedpractitioner, you'll find thisrefreshed book more than lives up to its reputation. ProgrammingPython, 3rd Edition, teaches you the rightway to code. It explains Python language syntax and programmingtechniques in a clear and concisemanner, with numerous examples that illustrate both correct usage and.